Pengaruh Disiplin Kerja, Stres Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Sardana Indah Berlian Motor - Valencia Vierri; Melkyory Andronicus; Christina Anggraini; Sri Rahayu (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to examine the impact of discipline,stress and satisfaction on employee performance at PT Sardana Indah Berlian Motor. Respondent as many as 92 employees. This study applies a quantitative approach. The use of data is questionnaires, interviews and documentation. Data analysis techniques using multiple linear regression análisis. The results obtained that partially and simultaneously work discipline, work stress and job satisfaction have a positive and significant effect on employee performance at PT Sardana Indah Berlian Motor. Keyword:Discipline,Stress,Satisfaction,Performance.